Micromorphological studies on tribe Merremieae (Convolvulaceae) - Dhara G. RAMOLIYA; Vinay M. RAOLE; Kishore S. RAJPUT (Notulae Scientia Biologicae)
Research in micromorphology is essential for comprehending the taxonomy and systematic categorization of plants. Micromorphological attributes, including the characteristics of the leaf epidermis, stomatal complexes and trichome types, play a crucial role in species identification. This comprehensive microscopic examination enhances our ability to distinguish between closely related taxa and facilitates the verification of species. Although there have been advancements in classification of the family Convolvulaceae, there is still a need to investigate how some microscopic qualities can help clarify taxonomic problems within the tribe Merremieae, particularly at the generic level. This study has discovered various types of stomata in the examined species. These include paracytic, brachyparacytic, anisocytic, desmocytic, isotricytic and anisotricytic stomata. The trichome study revealed the presence of both glandular and eglandular types in different species. This provides detailed insights into the morphological diversity of stomata and trichomes within the Convolvulaceae family. The results highlight the significance of conducting a thorough micromorphological examination to enhance the accuracy of taxonomic categorizations within the Merremieae tribe and Convolvulaceae family. Single Linkage Cluster Analysis (UPGMA) enabled the establishment of strong intergeneric links, leading to a more precise understanding of evolutionary connections and affirming previous taxonomic modifications. These observations improve the precision of identifying different species and provide significant information for future studies.